MILITARY INTERVENTION IN THE GAMBIA: LESSONS FROM THE IVORY COAST, LIBERIA AND SIERRA LEONE - M. Svicevic (BRICS Law Journal)
This article analyses the recent Economic Community of West African States (ECOWAS) military intervention in the Gambia, primarily focusing on possible legal bases for the enforcement action. It examines the political situation following the release of the election results and details the international response to the post-election situation in the Gambia. Among the legal bases assessed include United Nations Security Council authorisation of regional enforcement action under Chapter VIII of the U.N. Charter through Resolution 2337 (2017), intervention by invitation and consent through prior treaty. In so doing, the article also illuminates the plausibility that the ECOWAS military intervention may be considered as unilateral enforcement action, a point further stressed through an analysis of prior ECOWAS interventions, most notable, the interventions into Sierra Leone and Liberia. Moreover, the intervention in the Ivory Coast following the 2010-2011 postelection crisis is also examined in showcasing the situational similarities between those in the Ivory Coast and those in the Gambia. In so doing, the article inter alia, explores the international legal framework pertaining to the prohibition of the threat and use of force; analysing its nature as well as exceptions to it. Article 2(4) of the U.N. Charter, read together with Article 53, therefore form the backbone of the contribution.